Anatomy in Competencies-Based Medical Education - Erich Brenner (MDPI AG, 2022)
Anatomy as a basic science discipline is "vanishing" in recent competencies-based medical curricula. The fundamental requirement of these curricula to apply the knowledge from the basic disciplines in practical and clinical everyday life contributes to this disappearance. Anatomical educational objectives are in many cases not yet adapted to these changes. At the same time, the higher levels of the progress dimension in the cognitive domain and the activities associated with them certainly allow the application; even the analysis or evaluation of anatomical knowledge. However, a change in the teaching objectives to these higher levels of the progress dimension must also be accompanied by a change in the anatomical assessments. Since these forms of examinations themselves represent a practical application of anatomical knowledge, they must be carried out on suitable examination material. However, in order to protect living persons, the donated body again comes into focus.